ПРИНЦИПИ УДОСКОНАЛЕННЯ БАГАТОРІВНЕВИХ АВТОНОМНИХ ІНВЕРТОРІВ НАПРУГИ - Волков, І.В.; Голубєв, В.В.; Зозульов, В.І. (Інститут електродинаміки Національної академії наук України, 2021)
The article considers the properties of the most commonly used two-and multilevel inverter topologies used in systems for converting electricity from several primary power sources into the required high-quality output voltage for low-voltage networks and high-voltage consumers. However, a common disadvantage of most known multilevel converters is the increasing complexity of power structures, an increase in the number of primary power sources, power elements, and the cost of devices as the number of their voltage levels increases. Two schemes of alternative three-level autonomous voltage inverters with a high-frequency autotransformer with a midpoint and an example of constructing their digital control system are proposed. The analysis of their work on PSpice models in the OrCAD design system is carried out. The possibility of obtaining six voltage sublevels with fewer power elements and increased output voltage quality is shown, compared to the corresponding cascade multilevel inverters. The advantages and applications of autotransformer bridge voltage inverters in terms of energy and functionality compared to well-known multilevel inverters are presented. Ref. 8, fig. 7.